2013
DOI: 10.1021/cm304067d
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Conducting Features of Niobium-Doped Lanthanum Tungstate, La27(W1–xNbx)5O55.55−δ

Abstract: The most studied ceramic proton conductors are those based on the perovskite structure. However, these materials have some practical drawbacks including their poor tolerance to carbonation. Hence, proton-conducting ceramic materials with fluorite structure are currently under investigation. One of the most studied materials is the lanthanum tungstate, “Ln6WO12”. Here, we report a new series of compounds La27W5–5x Nb5x O55.5–5x/2□8.5+5x/2 obtained by niobium doping to optimize/increase the amount of oxygen vaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
57
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 39 publications
2
57
3
Order By: Relevance
“…These conductivity values are somewhat lower than those previously reported for dense pellets prepared from nanosized powders obtained by freeze-drying precursors and uniaxial pressing into disks, i.e. 4 Á 10 À 3 S cm À 1 at 800 1C (wet atmosphere) [14]. These differences are clearly related to the much reduced particle size and better densification of the ceramics by applying high pressures.…”
Section: S7 -10bp S7 -20bpcontrasting
confidence: 59%
See 2 more Smart Citations
“…These conductivity values are somewhat lower than those previously reported for dense pellets prepared from nanosized powders obtained by freeze-drying precursors and uniaxial pressing into disks, i.e. 4 Á 10 À 3 S cm À 1 at 800 1C (wet atmosphere) [14]. These differences are clearly related to the much reduced particle size and better densification of the ceramics by applying high pressures.…”
Section: S7 -10bp S7 -20bpcontrasting
confidence: 59%
“…Fig. 6c 2θ (º) S10-10BP 1600ºC/10h S10-20BP 1600ºC/10h S10-10BP 1600ºC/20h S10-20BP 1600ºC/20h [7,14] where the same composition was heated at 1600 1C and W losses were not observed either.…”
Section: S7 -10bp S7 -20bpmentioning
confidence: 95%
See 1 more Smart Citation
“…[23][24][25] Escolástico et al 26 found that the H 2 permeation flux through a La 5.5 WO 11.25-δ membrane only changed slightly over 72 h when using a mixture of 15% CO 2 in Ar as a sweep gas at 800°C.…”
mentioning
confidence: 99%
“…In this report, the synthesis and study of a new series of materials (La 1−x K x ) 27.08 W 4.92 O 55.38−θ (y = 0.92, the (La,K)/W ratio is 5.5) prepared with K + partial substitution for La 3+ to improve the conductivity. Besides, mechanical property is regarded as an important characteristic in practical applications besides their electrical property.…”
Section: Introductionmentioning
confidence: 99%